Evaluation of Hylan G-F 20 Treatment with Opioid Prescriptions and Intraarticular Corticosteroid Injections in Patients with Osteoarthritis of the Knee Using a Claims Database. (December 2021) - Langworthy, Michael J.; Hummer, Charles D.; Ngai, Wilson; Hao, Lichen; Webner, David
Objective: Assess how treatment with the viscosupplement hylan G-F 20 relates to opioid prescriptions and intraarticular corticosteroid injections (IACS) in patients with osteoarthritis of the knee (OAK). Design: Case-crossover; adult patients with OAK identified in a claims database were treated with hylan G-F 20 from July 1, 2007, to June 29, 2017. Opioid or IACS prescriptions in the 6 months before treatment were compared to the 6 months after. Patients with comorbid conditions requiring pain medications were excluded, resulting in a 29, 395-patient cohort. Four subgroups were investigated: patients with (1) opioids before hylan G-F 20 (OB; n = 6, 609); (2) opioids before and after hylan G-F 20 (OBF; n = 3, 320); (3) IACS before hylan G-F 20 (CB; n = 11, 162); and (4) IACS before and after hylan G-F 20 (CBF; n = 2, 810). All opioids were converted to morphine milligram equivalents (MME). Results: OB subgroup patients had a significant decrease ( P < 0.01) in total MME (−14.0%), MME per day (−14.2%) and opioid prescription days (−12.6%) after treatment versus before. Only 50.2% of patients prescribed opioids before hylan G-F 20 were prescribed an opioid after treatment. OBF subgroup patients had a significant increase ( P < 0.01) in opioid prescription days (7.8%) before versus after treatment. There was a significant decrease ( P < 0.01) in the number of IACS after versus before treatment for the Total Cohort (−56.1%), and subgroups CB (−72.6%) and CBF (−4.1%). A total of 74.8% of patients receiving an IACS before treatment did not receive an IACS after treatment. Conclusions: Hylan G-F 20 is associated with a reduction in opioid prescriptions and IACS in OAK patients.